DNA adducts induced by in vitro activation of extracts of diesel and biodiesel exhaust particles. (19th September 2015) - Ross, Jeffrey A.; Nelson, Garret B.; Mutlu, Esra; Warren, Sarah H.; Gilmour, M. Ian; DeMarini, David M.
Abstract: Context : Biodiesel and biodiesel-blend fuels offer a renewable alternative to petroleum diesel, but few data are available concerning the carcinogenic potential of biodiesel exhausts. Objectives : We compared the formation of covalent DNA adducts by the in vitro metabolic activation of organic extracts of diesel-exhaust particles (DEP) from petroleum diesel and soy biodiesel and correlated DNA adduct levels and mutagenicity in Salmonella TA100. Methods : We examined two different DEP from petroleum diesel (C-DEP and B0), one from soy bean oil biodiesel (B100) and one from combustion of a blend of 20% B100 and 80% B0 (B20) for in vitro DNA adduct-forming potential under oxidative or nitroreductive conditions in the presence of calf thymus DNA as well as in vivo in Salmonella TA100. The modified DNA was hydrolyzed and analyzed by 32 P-postlabeling using either butanol extraction or nuclease P1 pre-enrichment. Results : Multiple DNA adducts were produced with chromatographic mobilities consistent with PAH and nitro-PAH adducts. The types and quantities of DNA adducts produced by the two independent petroleum diesel DEP were similar, with both polycyclic aromatic hydrocarbon (PAH)- and nitro-PAH-derived adducts formed. Relative potencies for S9-mediated DNA adduct formation, either per mass of particulate or per MJth energy consumed were B100 > B0 > B20. Conclusions : Soy biodiesel emissions induced DNA damage in the form of presumptive PAH and nitro-PAH DNA adducts that correlated with mutagenicity in Salmonella . B20 is the soy biodiesel used most commonly in the US, and it produced the lowest DNA adduct-emission factor, ∼50% that of petroleum diesel.